Respuesta :
Again, let's use the difference of squares.
a^2-b^2= (a+b)(a-b)
16x^2-1
(4x+1)(4x-1)
Final answer: (4x+1)(4x-1)
a^2-b^2= (a+b)(a-b)
16x^2-1
(4x+1)(4x-1)
Final answer: (4x+1)(4x-1)
This is an example of difference of squares factoring
Here is how you can deal with it;;;
[tex]16x^2-1=(4x)^2-1^2[/tex]
the first term is the square of 4x and the second one is the square of 1
then, you can write:
[tex][(4x)-1]*[(4x)+1]=[4x-1][4x+1][/tex]
Done...
Hope you got the idea
Here is how you can deal with it;;;
[tex]16x^2-1=(4x)^2-1^2[/tex]
the first term is the square of 4x and the second one is the square of 1
then, you can write:
[tex][(4x)-1]*[(4x)+1]=[4x-1][4x+1][/tex]
Done...
Hope you got the idea